PELATIHAN MENGHIAS TOTE BAG MENGGUNAKAN DAUN DI SEKITAR RUMAH UNTUK MENDORONG PRODUKTIVITAS DESA TUIREJO KECAMATAN KEDAMEAN KABUPATEN GRESIK - Ujik Nur Asiah; Rizky Primadani Primadani; Teguh Priyono; Cantika Nur Intania; Dimas Uzlifatul Jannah; M. Syifaul Fuadi; Khoiriyah; Habiburrahman; Arif Mahya Fanny (Universitas PGRI Adi Buana Surabaya, 2023)
Reducing plastic waste is a shared responsibility not only for the government through making regulations such as PERDA (Regional Regulation), but also society as a whole. One thing that can be done is to use a shopping bag that can be used many times, for example a tote bag or tote bag. There are lots of different types of tote bags, ranging from the plain ones to the different looks. In addition to being able to use plain tote bags, they can also be decorated to make them look nicer and can also be resold. Because of this, training and practice of decorating tote bags was carried out. The activity was carried out by providing counseling as well as practice and assistance to members of youth organizations and youth women's mosques in Turirejo Village, Kedamean District, Gresik Regency by utilizing existing plant leaves for materials for making ecoprint tote bags. The purpose of this activity is to increase the creativity and productivity of youth members and mosque youth who are expected to become ecoprint tote bag craftsmen, as well as economic empowerment which is expected to increase income and encourage increased welfare. The methods and stages of the activities carried out are conducting material presentations then followed by live demonstrations and practice of making ecoprint tote bags. The result of this training is that members of youth organizations and mosque youth have become more trained in making ecoprint tote bags. It is hoped that the skills acquired can encourage creativity, productivity and the economy. From a small existing group, it can become bigger by creating a business unit with a variety of other products on the basis of an ecoprint that can prosper the surrounding community, especially Turirejo Village.